Augmented reality : an emerging technologies guide to AR - Kipper, Gregory; Rampolla, Joseph (Elsevier, Syngress, 2013)
"With the explosive growth in mobile phone usage and rapid rise in search engine technologies over the last decade, augmented reality (AR) is poised to be one of this decade's most disruptive technologies, as the information that is constantly flowing around us is brought into view, in real-time, through augmented reality. In this cutting-edge book, the authors outline and discuss never-before-published information about augmented reality and its capabilities. With coverage of mobile, desktop, developers, security, challenges, and gaming, this book gives you a comprehensive understanding of what augmented reality is, what it can do, what is in store for the future and most importantly: how to benefit from using AR in our lives and careers. Educates readers how best to use augmented reality regarless of industryProvides an in-depth understanding of AR and ideas ranging from new business applications to new crime fighting methods Includes actual examples and case studies from both private and government applications."--Resumé vydavatele
Terminologický slovník
Keywords: rozšířená realita; augmented reality; příručky; elektronické knihy; handbooks and manuals; electronic books